Some Reflections on Comparative Advantage as it applies to CGIAR - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2022)
For years, CGIAR stakeholders have sought to define the System's comparative advantage (CA). With this concept note, ISDC aims at putting the concept of CA to effective use in research portfolio management at all levels within CGIAR, now that the One CGIAR structure makes portfolio approaches possible and especially salient. Built on this concept note, ISDC will propose a framework co-designed with CGIAR stakeholders to enable CGIAR funders, research managers and scientists to assess if and where CA exists, as well as where it might be desirable to invest in establishing CA where it does not presently exist.